Evaluasi Playability dengan Player Persona menggunakan Metode Heuristic Evaluation of Playability (HEP) pada Game Vainglory - Mochammad Naufal Rizky Angkasa; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Vainglory game is a Multi-player Online Battle Arena (MOBA) game which was released on July 28, 2018 on the PC platform which until June 26, 2019 is still under development or Alpha status. Playability is a term used to describe the quality of the game as a whole, which includes uses and aspects of the game, Playability is an important factor when determining the success or failure of a video game in providing an interesting gaming experience for its players. In this study begins with making a player persona, by conducting interviews directly with 6 respondents who are players from the Vainglory game, which aims to determine the characteristics and categories of respondents when playing the Vainglory game. To be able to find out the playability aspects of the Vainglory game, an evaluation using the Heuristic Evaluation For Playability method is an evaluation method specifically devoted to evaluating the game at the development stage. This study aims to get playability problems in the Vainglory game. The evaluator used in this study was divided into two groups, namely 3 evaluators who had the ability to develop games and 3 evaluators who had experience playing games with similar genres. The results of the Playability evaluation in the Vainglory game show the results of Severity Ratings namely Minor Usability Problem, the problems found in the Vainglory game have the potential to cause problems or disruptions to players that cause a sense of playing experience or the player's playing experience to be bad.